5′-Long Terminal Repeat-Selective CpG Methylation of Latent Human T-Cell Leukemia Virus Type 1 Provirus In Vitro and In Vivo - Koiwa, Tsukasa (American Society for Microbiology, 2002)
CpG methylation of the human T-cell leukemia virus type 1 (HTLV-1) long terminal repeat (LTR) has been implicated in proviral latency, but there is presently little information available regarding the pattern of LTR methylation and its effect on viral gene expression. To gain insight into the mechanisms of HTLV-1 latency, we have studied methylation of individual CpG sites in the U3-R region of the integrated proviral LTR by using bisulfite genomic sequencing methods. Surprisingly, our results reveal selective hypermethylation of the 5′ LTR and accompanying hypomethylation of the 3′ LTR in both latently infected cell lines and adult T-cell leukemia (ATL) cells having a complete provirus. Moreover, we observed a lack of CpG methylation in the LTRs of 5′-defective proviruses recovered from ATL samples, which is consistent with the selective hypomethylation of the 3′ LTR. Thus, the integrated HTLV-1 provirus in these carriers appears to be hypermethylated in the 5′ LTR and hypomethylated in the 3′ LTR. These results, together with the observation that proviral gene expression is reactivated by 5-azacytidine in latently infected cell lines, indicate that selective hypermethylation of the HTLV-1 5′ LTR is common both in vivo and in vitro. Thus, hypermethylation of the 5′ LTR appears to be an important mechanism by which HTLV-1 gene expression is repressed during viral latency.